A cultural political economy of supply-side subsidies for private schools in Argentina - Moschetti, Mauro Carlos; Lauria Masaro, Mauro (Education Policy Analysis Archives, 2020)
In comparison with other forms of public-private partnerships (PPP) in education of more recent emergence such as voucher programs or charter schools inspired by the postulates of the theory of public choice, supply-side subsidies for private schools usually respond to less explicit theories of change. Indeed, most of these policies are addressed by specialized literature as unique and highly idiosyncratic arrangements, rather than examples of a particular variety of PPP. The frequent absence of a theory of change that explicitly presents the assumptions, objectives and mechanisms of this type of policy, makes it necessary to reconstruct it from a perspective of policy sociology based on the analysis of the behavior of agents and economic, political, institutional and cultural drivers that lie behind their adoption in each particular context. Based on a review of the literature and the analysis of the legislative debates of the 1947-2006 period, this article seeks to examine the process of adoption of the regulatory framework defined by the policy of supply-side subsidies for private schools in Argentina from an evolutionary perspective of political and cultural economy. The article distinguishes three periods for analytical purposes among which an evolutionary logic of nonlinear continuity prevails, subject to the contextual vagaries and driven by different actors in the field of ideas and political practice.